The Dynamic Linkages between Stock Market and Foreign Exchange Market: Evidence from an Emerging Market - Zaiane, Salma; Jrad, Rabeb (International Journal of Economics and Financial Issues, 2020)
The paper investigates the dynamic linkages between exchange rate (against US dollar) and the stock market (local currency) of Tunisia from January 2004 to April 2017. In particular, the paper tries to answer if there are any correlations between these variables and how they move in high volatile periods. By using a VEC model and applying the techniques of Granger Causality test, we conclude the existence of a unidirectional relationship between the two variables (from stock prices to exchange rate). Due to persistent long memory and the presence of the asymmetric effect in both markets, we estimate the dynamic correlations between these variables using DCC-FIAPARCH model. Results reveal that volatility shocks create abrupt changes in the dynamic correlations. However, this effect is only short term and do not sustain between consecutive high volatility regimes. Thus, policymakers and investors do not need to be concerned about long run contagion effects. Accordingly, financial managers can obtain more insights in the management of their international portfolio affected by these two variables. This should be particularly important to domestic as well as international investors for hedging and diversifying their portfolio mainly by predicting the path of the exchange rate. Keywords: Stock Market, Foreign Exchange Market, VECM, Granger Causality, DCC-FIAPARCH JEL Classifications: D53, F31 DOI: https://doi.org/10.32479/ijefi.9623